Children's voice and agency in diverse settings : international research and perspectives - Beaton, Mhairi; Burke, Anne M. (Anne Michelle), 1966-; Keskitalo, Pigga, 1972-; Turunen, Tuija (New York : Routledge, 2024)
"This book outlines the key findings from the ADVOST project and other international projects that examine how educational practitioners have utilised theoretical notions of voice and agency to enhance the social inclusion and wellbeing of children within their settings. Bringing together findings from three project case studies that are each placed in a different national context, chapters explore theoretical principles of space, audience and influence to facilitate and enhance the voices of very young children. Focusing on diversity as an opportunity rather than a challenge, the book provides collaboratively written and regionally diverse chapters that ultimately contribute to a growing field on literature examining how young people might be included in culturally sensitive and responsive ways within education, recognising the diversity that young people, their families and communities bring to educational processes to provide an inclusive education for all. Offering multiple perspectives and insights into our growing understanding of children's voice and agency in diverse settings, this book will be of relevance to scholars, researchers and academics in the fields of primary education, multicultural education, early years and educational research, and child development studies"--
Part 1. Key Theoretical Ideas. Introduction -- Being well, being in the community, having voice and agency through practical philosophy -- An exploration of practices for rights-based education through promoting voice in the early years: Building a spider's web -- The sociomateriality of voice and its implications for research with children: Voice-as-event in an intergenerational art program -- Part 2. ADVOST Case Studies. Children's Identity and Agency in an Art Gallery: Voices in the Making -- Using Children's Literature to Augment Children's Multimodal Voices and Agency: Placelessness in the Classroom -- Teachers' perspectives on Sami culture-based pedagogical innovations promoting children's agency in online Sami language classes -- Exploring Sámi language instruction for young learners: Comparative case studies in Finland and Norway -- Space and Time as Pedagogical Tools for Facilitating Voice and Agency -- An approach to developing community that supports voice and agency in education settings: Circles of Trust -- Advancing Young Children's Inclusion and Agency in Society Through Voice and Story: A Reflection.
Keywords: Early childhood education -- Research -- Methodology; Culturally relevant pedagogy; Right to education -- Cross-cultural studies; Education, Bilingual -- Cross-cultural studies; Immigrant children -- Education (Early childhood) -- Cross-cultural studies; Indigenous children -- Education (Early childhood) -- Cross-cultural studies; Sami (European people) -- Education (Early childhood); Sami language -- Study and teaching; EDUCATION / General